Acknowledgment to Reviewers of Pharmaceutics in 2020 - Pharmaceutics Editorial Office (MDPI AG, 2021)
Peer review is the driving force of journal development, and reviewers are gatekeepers who ensure that Pharmaceutics maintains its standards for the high quality of its published papers [...]